2017
DOI: 10.1002/2016jc012622
|View full text |Cite
|
Sign up to set email alerts
|

Hydrographic and fish larvae distribution during the “Godzilla El Niño 2015–2016” in the northern end of the shallow oxygen minimum zone of the Eastern Tropical Pacific Ocean

Abstract: Based on hydrographic data and vertical distributions of tropical species of fish larvae (Diogenichthys laternatus, Vinciguerria lucetia, Bregmaceros bathymaster, and Auxis spp.), effects of “Godzilla El Niño 2015–2016” in the shallow oxygen minimum zone off Mexico were analyzed. Zooplankton samples were collected during four cruises, before (February 2010 and April 2012) and during (June 2015 and March 2016) the warm event. Temporal series of sea surface temperature revealed that June 2015 was the warmest Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…The exit of GCW was observed on the peninsular side as a front with high salinity (Castro et al, 2006;Collins et al, 2015) as was the entrance of TW over the continental platform in front of the coasts of Sonora, in accordance with the typical circulation scheme for this zone (Lavín et al, 2009). The depth of the oxycline was shallow in comparison to the region of Cabo Corrientes, but the intensity of the oxycline was amongst the lowest recorded (Sánchez-Velasco et al, 2017). This is due to the GCW being more oxygenated and dominating depths below 150 m (Figures 3, 5), causing the oxycline to become the thickest in this region.…”
Section: Entrance To the Gulf Of California (Region Iii)supporting
confidence: 63%
See 1 more Smart Citation
“…The exit of GCW was observed on the peninsular side as a front with high salinity (Castro et al, 2006;Collins et al, 2015) as was the entrance of TW over the continental platform in front of the coasts of Sonora, in accordance with the typical circulation scheme for this zone (Lavín et al, 2009). The depth of the oxycline was shallow in comparison to the region of Cabo Corrientes, but the intensity of the oxycline was amongst the lowest recorded (Sánchez-Velasco et al, 2017). This is due to the GCW being more oxygenated and dominating depths below 150 m (Figures 3, 5), causing the oxycline to become the thickest in this region.…”
Section: Entrance To the Gulf Of California (Region Iii)supporting
confidence: 63%
“…In southern latitudes, below 22 • N for coastal stations and 20.5 • N for oceanic stations, the surface layer was dominated by the incursion of TSW. Its anomalous presence was related to the seasonally expected pattern, associated with a developing ENSO event (Sánchez-Velasco et al, 2017). In this region, the greatest stratification in our study period was registered, from 1000 to 1400 J•m −3 along an ocean-coast gradient ( Figure 9A).…”
Section: June 2015 Cabo Corrientes (Region I)mentioning
confidence: 51%
“…The warm anomalies impacted the Bering Sea from 2014 until 2016 by shifting phytoplankton blooms to early spring (Stabeno et al, 2017), similar to the early increase in phytoplankton abundance observed in the Gulf of Alaska in 2014 (Peña et al, 2019) and early NCP from this work (Figure 4c). Still, in 2015, there was a decline in zooplankton stocks off the coast of Mexico and a shift in the vertical distribution of fish larvae in response (Sánchez-Velasco et al, 2017). Still, in 2015, there was a decline in zooplankton stocks off the coast of Mexico and a shift in the vertical distribution of fish larvae in response (Sánchez-Velasco et al, 2017).…”
Section: Environmental Consequences Of the 2013-2016 Warm Events And mentioning
confidence: 99%
“…The development of the Arc pattern along the west coast of United States between 2014 and 2015 altered the local phytoplankton community structure (Du & Peterson, 2018), with elevated SSTs stimulating harmful algae blooms in the northern California Current (McKibben et al, 2017;Zhu et al, 2017). Still, in 2015, there was a decline in zooplankton stocks off the coast of Mexico and a shift in the vertical distribution of fish larvae in response (Sánchez-Velasco et al, 2017). For the first time on record, the northeast Pacific Ocean was a pCO 2 source (Sutton et al, 2017) at the same time that net organic carbon production declined in 2015 (Figure 5a).…”
Section: Environmental Consequences Of the 2013-2016 Warm Events And mentioning
confidence: 99%
See 1 more Smart Citation